Fillers for Polymer Applications - Rothon, Roger (Polymers and Polymeric Composites: A Reference Series,, 2017)
This handbook provides an introduction to and reference information about the science behind the production and use of particulate fillers in polymer applications. Fillers play an important role and are used with practically all types of polymers: thermoplastics, thermosets, elastomers. Readers will find an introduction to the topic of particulate fillers for polymer applications and their importance. The first chapters describe the use and characteristics of fillers in different polymer types, such as thermoplastics, thermosets and elastomers. The following chapters compile and summarize comprehensive information about different filler materials which find application nowadays, including mineral fillers (for example feldspars, wollastonites, and many more) and inorganic fillers (barium sulphate, or clays), bio-fillers, recycled and sustainable fillers, and fillers for specific applications (for example flame-retardant fillers, fillers for electrically conductive applications, or thermally conductive additives). Offering key information, compiled by a mixed team of authors from academia and industry, this handbook will appeal to researchers and professionals working on and with particulate polymer fillers alike.- Resumé vydavatel